THE ROLE OF BK SUPERVISORS IN IMPROVING THE PROFESSIONALIZATION OF BK TEACHERS IN SCHOOLS IN THE ERA OF SOCIETY 5.0 - Alnetia Dwi Kamirsa Amria; Firman Firman; Neviyarni Neviyarni; Muhammad Asyraf Bi Che Amat (Consilium: Education and Counseling Journal, 2023)
BK supervisors are educational staff who have an important role in increasing the professionalism of BK teachers and the quality of education in schools. Supervision is carried out starting from program planning, program implementation and evaluation of guidance and counseling teacher supervision. The supervision provided by the supervisor of the BK teacher will also support student success. Patterns of guidance and counseling are in the realm of personal, learning, social and career fields. In the era of society 5.0, human life is facilitated by technology. To face the socity 5.0 era, counseling teachers need to make a paradigm shift in carrying out their service duties at school. For this reason, good supervision is also needed by the BK supervisor so that the professionalism of BK teachers increases in this era of society 5.0. Today, counseling supervisors do not come from the guidance and counseling discipline. As a result, the supervisor's role becomes less effective in assessing the performance of counseling teachers and their programs so that the implementation of counseling is not carried out as it should. The purpose of this study is that stakeholders should consider choosing BK supervisors where BK supervisors come from the field of guidance and counseling as well as increasing the professionalism of BK teachers in the era of society 5.0 in implementing the overall guidance and counseling process. This research is a qualitative research using literature study method. The results of this study indicate that the role of the counseling supervisor in schools carries out proper supervision of program planning, implementation, assessment and reports on the supervision they carry out on the implementation of counseling services in schools using technology in the era of society 5.0.